Trial by fury - Jance, Judith A., 1944- (Avon suspence, 1986)
The dead body discovered in a Seattle dumpster was shocking enough-but equally disturbing was the manner of death. The victim, a high school coach, had been lynched, leaving behind a very pregnant wife to grieve over his passing, and to wonder what dark secrets he took to his grave. A Homicide detective with twenty years on the job, J.P. Beaumont knows this case is a powder keg and he fears where this investigation will lead him. Because the answers lie on the extreme lethal edge of passion and hate, where the wrong kind of love can breed the most terrible brand of justice